Ethical Challenges in Global Health Research - Waechter, Randall; Coomansingh, Kareem; Macpherson, Cheryl; Sarma, Sameera (Springer Nature Switzerland, 2024)
Understanding global health ethics requires insight into factors that influence inequalities in global health such as economic disparities, extreme poverty, limits on human rights, political oppression, and unequal distribution of research funding. We review some ethical issues related to global health, focusing on global infectious disease research. Significant ethical concerns include inequities and disparities in national and institutional capacity to conduct global health research on infectious diseases because these can influence the extent to which low-resource countries benefit from the research. Research funding for global health or infectious disease often comes from the governments and institutions of developed countries. It is allocated based on their institutional priorities, which may not align with those of the developing country. When they do align, developing countries may lack the necessary research, manufacturing, and logistical capacity to discover, produce, and distribute medicines and/or vaccines for infectious diseases within their countries. Research ethics guidelines evolve iteratively to help global health practitioners and researchers navigate concerns involving global health and infectious disease. There is an ongoing need for legal and regulatory frameworks, support for research capacity building—including ethics capacity, and systems to audit the impacts of capacity-building programs. While partnerships are essential to carrying out global health research, inequities between high- and low-resource countries drive ethical challenges in global health and infectious disease work. Recognizing and mitigating these inequities is a core challenge in global health research ethics supported by wider efforts toward decolonization.